2009
DOI: 10.1603/029.102.0241
|View full text |Cite
|
Sign up to set email alerts
|

Local Infestation or Long-Distance Migration? The Seasonal Recolonization of Dairy Farms by <I>Stomoxys calcitrans</I> (Diptera: Muscidae) in South Central Ontario, Canada

Abstract: Stable fly (Diptera: Muscidae) populations in south central Ontario, Canada, first occur on dairy farms in late spring, grow exponentially throughout the summer, and are frozen back each autumn. We examined the extent of overwinter persistence on 22 dairy farms in a 55- by 60-km region north of Lake Ontario that spans four climatic zones. Our overwintering sampling of larval habitat identified three farms located in the southern section of the study region as potential overwintering refugia. Using sticky trap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…Males and young females especially have been reported to leave when population densities are high (Scholl 1986, Hogsette et al 1989, which can be attributed to increasing levels of intraspeciÞc competition. However, Beresford and Sutcliffe (2009) claim that spring dispersal of female stable ßies from farms in south central Ontario, Canada, was not densitydependent.…”
Section: Discussionmentioning
confidence: 94%
“…Males and young females especially have been reported to leave when population densities are high (Scholl 1986, Hogsette et al 1989, which can be attributed to increasing levels of intraspeciÞc competition. However, Beresford and Sutcliffe (2009) claim that spring dispersal of female stable ßies from farms in south central Ontario, Canada, was not densitydependent.…”
Section: Discussionmentioning
confidence: 94%
“…Overwintering stable ßy larvae have been observed in heat generating substrates such as silage (Scholl et al 1981) and occasional adults have be observed on traps, even in mid winter (Berkebile et al 1994). Continuous breeding, possibly in climate controlled environments such as dairies or heated barns (Beresford and Sutcliffe 2009), and overwintering are a potential sources for the early season ßies, however, Þnding overwintering ßies has proven to be very difÞcult. Jones et al (1999) postulated that stable ßies passively migrate long distances on frontal systems, permitting southern populations to recolonize the northern portions of their range each year.…”
Section: First Emergencementioning
confidence: 99%
“…Our use of a 10ЊC base for development is based on PruessÕs (1983) recommendation for a standardized base to be used in pest management (e.g., Beresford and Sutcliffe 2009b). We used weather station data, which is obtained from a Stevenson screen in which thermometers are set 1.2Ð2 m high (Barry and Chorley 1976).…”
Section: Discussionmentioning
confidence: 99%